Cloud Computing for Improving Work Efficiency at the Belibi Village Government Office in the Era of Transformation - Kurniasih Mika; Ocky Sundari Rahardjo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Digital transformation has become a crucial element in improving work efficiency within the government sector, including in remote areas such as Belibi Village, Central Kalimantan. This study aims to describe the implementation process of cloud computing, identify the challenges faced, and formulate strategies to improve work efficiency in the Belibi Village Government Office. Using a descriptive qualitative approach, data were collected through in-depth interviews and observations with village officials and community figures. The findings show that although cloud computing offers significant benefits such as efficient data storage and online collaboration, its implementation is still hindered by weak digital infrastructure, low technological literacy among staff, and the absence of formal training. Suggested strategies include improving internet access, providing supporting devices, offering technical training, and collaborating with cloud service providers. This study concludes that digital transformation in village governance requires a gradual approach and comprehensive policy support to ensure successful and sustainable implementation.